Trends of caesarean section: an analytical overview of indications - Gavhane, Shruti A.; Chaudhari, Shilpa N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Caesarean section is one of the commonly performed surgical procedures in obstetrics. An increasing trend has been observed in both primary and repeat caesarean sections. The reasons for its increase are multifaceted. So, this study was carried out to compare the rates of caesarean delivery and to analyse various indications contributing to it. Methods: This retrospective study was conducted over a period of three year from 1st January 2016 to 31st December 2018 at the department of obstetrics and gynaecology, tertiary care hospital Pune, Maharashtra, India. All caesarean delivery (primary and repeat) taken place during the study period. The rate and indications of caesarean section was calculated over the study period to find out the trends in caesarean delivery. The data so collected was presented with graphical representation. Statistical analysis was performed with SPSS software and t-test was used for continuous data and pearson chi square test for discrete data. Results: There were a total of 12373 deliveries during the study period out of which, 3701 had delivered via Caesarean Section. So, the rate of caesarean section in the study was found to be 29.91%. Conclusions: Being a tertiary care hospital, a high rate of caesarean deliveries was observed, Individualization of the indication and careful evaluation, following standardized guidelines, practice of evidenced-based obstetrics and audits in the institution, can help us limit caesarean section rates.